Developing Flipbook-Based Electronic Instructional Materials to Improve Student Learning Outcomes in Social Studies - Himmatul Izzah; Luthfiya Fathi Pusposari; Jadzil Baihaqi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to develop flipbook-based electronic instructional materials for Social Sciences on the subject of Equitable Development and to determine the feasibility and effectiveness in improving student learning outcomes. The study used the Research and Development method with the ADDIE. The research subjects were 31 students of Class VIII B MTs Negeri 7 Malang. The research instruments included validation sheets of material and media experts, as well as learning outcome tests in the form of multiple choice questions with a one group pre-test and post-test design. Data were analyzed using normality tests and Paired Sample t-Test. The results indicate that the analysis phase identified need for interactive teaching materials for both teachers and students; the design steps produced a flipbook-based teaching material design aligned with learning outcomes and objectives; the development show the teaching materials were validated by subject matter and media experts, receiving ratings of